The Framing Analysis: Coloum Opinion In Newsweek Magazine - Pujoko, Pujoko (2005)
The objectives of the study are to describe the kinds of problem identification to describe the adverbs category that exist in column opinion in Newsweek Magazine. In this research, the writer uses qualitative approach. The writer collects the column opinion in Newsweek Magazine as the data. The data of the research are nine (9) column opinions taken from Newsweek Magazine from October-November. In finding the framing of the column opinion the writers refers to the theory of Abror, and to identify the adverbial category the writer employs the theory of Givon. Based on the result of analysis the writer finds that problem identification in column opinion (worldview) are; cognitive dissonance, empathy, packing and association. The adverbs category that exist in column opinion (worldview) are manner adverb, place adverb, time adverb, speaker's comment adverbs such as comments on desirability/rightness, comments on the characters or motives of the object and epistemic comments.